PENGARUH AKTIVITAS FISIK MAKSIMAL DAN EKSTRAK DAUN BAMBU MANGGONG (Gigantochloa manggong) TERHADAP AKTIVITAS KATALASE PADA HATI TIKUS PUTIH (Rattus norvegicus) - APRIANA, RIRIEN APRIANA; SUPRIYATIN, SUPRIYATIN; RAHAYU, SRI (Bioma, 2015)
ABSTRACT Gigantochloa manggong, one of endemic bamboo plant in Indonesia is suspected have potensial as an exogenous antioxidant. Exogenous antioxidant can help the activity of endogenous antioxidant on the body when overtraining occurs. Antioxidant can be measured by catalase enzymes activity. This present study was carried out to determine the effect of maximum physical activity and leaf bamboo extract on catalase activity in liver organ of rats. This research used experimental method with completely randomized design (cRD). The test groups were the control rats (E0R0), rats induced leaf extract (E1R0), rats treated swimming activity (E0R1) and rats induced leaf extract and swimming activity (E1R1). Data were analyzed by the two-way ANOVA statistical test. Bamboo leaf extract turned out to be non-toxic and leaf extract contained flavonoids, alkaloids, triterpenoids dan saponins. Catalase units in the control group = 1.00 unit/ml, the group which induced leaf extract = 0.89 unit/ ml, the group which treated maximum physical activity = 0.78 unit/ml and the group which treated maximum physical activity and induced leaf extract = 0.56 unit/ml. Based on statistical test, catalase activity no effect (p> 0,05) on rats. It was concluded that maximum physical activity can’t decreased catalase activity, leaf bamboo extract can’t increased catalase activity and there was no effect between maximum physical activity and manggong bamboo leaf extract on catalase activity in liver organ of rats. Keyword : antioxidant, catalase, manggong bamboo, physical activity